2009
DOI: 10.1007/s00228-009-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does the indicator “concurrent use of three or more psychotropic drugs” capture use of potentially inappropriate psychotropics among the elderly?

Abstract: Purpose The indicator "concurrent use of three or more psychotropic drugs" has been used as a measure of quality in drug use among the elderly. The aim of our study was to assess to what extent the indicator captures the use of specific psychotropics associated with an increased risk of adverse events among the elderly, i.e., potentially inappropriate psychotropic drugs (PIP). Methods All individuals aged 75 years and older in Sweden purchasing prescribed psychotropic drugs in 2006 constituted the study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The findings by Bell et al complement our previous research in which we assessed the extent to which the indicator captured use of potentially inappropriate psychotropic drugs (PIP) among the elderly [3]. We found that only one quarter of those using PIP had the indicator and concluded that clinical relevance should be balanced against convenience of use when selecting instruments to assess appropriateness in drug therapy in the elderly.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The findings by Bell et al complement our previous research in which we assessed the extent to which the indicator captured use of potentially inappropriate psychotropic drugs (PIP) among the elderly [3]. We found that only one quarter of those using PIP had the indicator and concluded that clinical relevance should be balanced against convenience of use when selecting instruments to assess appropriateness in drug therapy in the elderly.…”
supporting
confidence: 78%
“…We found that 72% of individuals with the indicator used PIP [3]. Thus, if a scan for specific drugs or combinations is unfeasible in quality assessments, the indicator may serve as a crude screening tool for inappropriate drug use.…”
mentioning
confidence: 90%
“…PICP was defined as concurrent utilisation of two or more benzodiazepines, two or more psychotropics in the same class (e.g., two or more hypnotics), and two or more anticholinergic psychotropics for a total of 40 days during 2006. The estimation of concurrent drug utilisation has been described previously [23]. Briefly, information on prescribers' dosage instructions is available only as a free text section in the register and is therefore not statistically processable.…”
Section: Methodsmentioning
confidence: 99%
“…Substance-specific population average PDDs were estimated for each psychotropic substance, thus enabling the calculation of theoretical treatment periods based on date of purchase and purchased amount. A detailed description of PIP and associated prevalence rates have been reported previously [23]. …”
Section: Methodsmentioning
confidence: 99%
“…To the Editor: We commend Lesén et al [1] for their excellent research investigating whether the quality indicator "concurrent use of three or more psychotropic drugs" captures use of potentially inappropriate psychotropic drugs (PIPs given to comorbid disease, and limited or unknown ability to predict poor health outcomes [3,4]. There is no evidence that potentially inappropriate drug use defined using Beers Criteria, the most widely cited explicit indicators, is associated with mortality or hospitalization among nursinghome residents [5].…”
mentioning
confidence: 99%